The effects of ascorbic acid on skeletal muscle blood flow in aged rats - Schwagerl, Peter J. (Kansas State University, 2010)
During exercise aged individuals exhibit endothelial dysfunction and decreased levels of whole-limb blood flow (BF), both of which may be linked mechanistically to age-related increases in reactive oxygen species (ROS). Ascorbic acid (AA) reduces levels of ROS and has been shown to alleviate vascular and hyperemic dysfunction at rest (Jablonski et al., 2007) and during small muscle mass exercise in humans (Kirby et al., 2009). However, the effect of AA on vascular function and BF to individual muscles during whole-body exercise is not known. PURPOSE: To test the hypothesis that a single high-dose infusion of AA would increase BF to the hindlimb musculature of old rats at rest and during treadmill running. METHODS: 18 old (~28 months) Fischer 344 x Brown Norway rats were randomized into rest (n=9) and exercise (n=9) groups. BF to the total hindlimb and individual muscles (28 individual muscles and muscle parts) was evaluated via radiolabeled microspheres before and after intra-arterial AA administration (76 mg/kg in 3 ml heparinized saline, 30 minute infusion) at rest and during submaximal treadmill running (20m/min, 5% grade). Total antioxidant capacity (TAC) and thiobarbituric acid reactive species (TBARS) were measured before and after AA to determine the ability of this specific dose of AA to increase levels of plasma antioxidants and decrease levels of ROS, respectively. RESULTS: At rest: AA increased TAC (~37%, P<0.05) but did not change TBARS (Pre: 6.8±0.7 vs Post: 7.0±1.0 µM, P>0.05). AA decreased total hindlimb BF (Pre: 25±3 vs Post: 16±2 ml/min/100g, P<0.05) and BF to 8 of the 28 muscles that were evaluated. During exercise: TAC was increased (~35%, P<0.05) and TBARS were decreased (Pre: 9.8±2.0 vs Post: 7.0±1.0 µM, P<0.05). However, there was no effect on either total hindlimb BF (Pre: 154±14 vs Post: 162±13, P>0.05) or BF to any of the individual muscles evaluated. CONCLUSIONS: Increased TAC via AA infusion reduces hindlimb muscle BF at rest but had no effect on BF during whole-body dynamic exercise. Thus, even though TBARS decreased, there was no evidence that AA supplementation increases blood flow to the locomotor muscles of old rats during whole-body exercise.
Keywords: Aging; Blood flow; Reactive oxygen species; Ascorbic acid; Exercise; Nitric Oxide; Biology, Animal Physiology (0433)